Efektivitas Sistem Administrasi Kependudukan Berbasis Teknologi Informasi (SAKTI) di Kota Kediri - Faizul Haq, Mohammad Raffi; Tukiman (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The Population and Civil Registration Service of the City of Kediri is one of the regional government agencies of the City of Kediri that implements acceleration of the quality of public services by presenting an innovation in public services in the field of population administration. One of the innovations is SAKTI (Information Technology Based Population Administration System), a website application that makes it easier for the people of Kediri City to manage population administration. The presence of the SAKTI Application does not necessarily replace face-to-face services at the Kediri City Population and Civil Registration Office. Some people prefer face-to-face services at the Kediri City Population and Civil Registration Office rather than online services via the SAKTI application. This research aims to determine and analyze the effectiveness of the Information Technology Based Population Administration System (SAKTI) at the Kediri City Population and Civil Registration Service. This type of research is qualitative research with a descriptive approach. Data collection techniques through observation, interviews and documentation. The theory used in this research is the theory of program effectiveness according to Budiani in Maulana & Adam (2021) with four focuses, namely accuracy of program targets, program socialization, program objectives, program monitoring. The research results show that the effectiveness of the SAKTI Application is still less effective. This is because there are still people who have not used the SAKTI Application to process population documents. Apart from that, there are still several problems with the SAKTI application.